The Influence Of Emotional Intelligence On The Performance Of Employees At The East Binjai District Office - Sari Humaira; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the influence of emotional intelligence on employee performance at the East Binjai District Office. This research was conducted with a causal associative quantitative approach. The sample used was all employees with a total of 85 people taken by prposive sampling. The results of the analysis show that emotional intelligence has a positive and significant effect on employee performance. Based on the hypothesis test, the t-count value of 44.133 is greater than the t-table 1.66412, with a significance value of 0.000 which is less than 0.05, which indicates that emotional intelligence plays an important role in improving employee performance. The regression coefficient shows that each increase in emotional intelligence units will lead to an increase in employee performance by 0.957 units, assuming other variables remain constant. In addition, the results of the determination test showed an Adjusted R Square value of 0.970 or 97%, which indicates that emotional intelligence has a very high influence on employee performance, while the remaining 3% is influenced by other factors that have not been studied. Thus, emotional intelligence is proven to have a significant influence on employee performance at the East Binjai District Office